Attitudes of Farm Outreach Professionals toward the use of Electronic Advisory Services in Punjab, Pakistan - Amir Riaz; Zaheeruddin Mirani; Muhammad Hamid Nawaz Khan; Fateh Muhammad Mari; Muhammad Ismail Kumbhar; Aijaz Ali Khooharo; Habibullah Magsi; Afia Naseem; Arif Masood; Syed Taimoor Shah (Social Science Review Archives, 2025)
This study attempted to examine the attitudes of agricultural extension agents, in this research termed Farm Outreach Professionals (FOPs), towards the use of electronic extension methods in five districts selected from Punjab, as well as the difficulties they face in applying these methods. The study also investigated how independent variables influenced the strength of these judgements. The sample includes around 86% of the 160 agricultural extension agents in the study population, with 138 having completed the questionnaires and met the research requirements. According to the findings, 64% of Punjab's agricultural extension agents had a positive attitude towards electronic agricultural extension approaches, while only 18% had a negative or indifferent one. The study also examined how independent variables influenced the strength of these judgements. The sample includes 180 Farm Outreach Professionals in the study population, with 160 of them completing questionnaires and meeting research requirements. According to the findings, 64% of Punjab's agricultural extension agents/FOPs had a positive attitude towards electronic agricultural extension approaches, while only 18% had a negative or indifferent one. The most significant impediments discovered were a lack of seriousness in applying these approaches and a lack of follow-up by agricultural extension agents on websites dedicated to electronic extension methods. The dependent variable was extension agents' attitudes towards electronic agricultural extension services, and the independent variables were "educational level," access to training in agricultural extension techniques, and the availability of electronic devices for extension agents, which were found to be significantly positively correlated at the 0.01 level. At the 0.01 level, there was a significant negative correlation between the dependent variable (extension attitudes) and the independent variable (age).